THE ROLE OF PHYSICAL EDUCATION IN IMPLEMENTING AN UNDERSTANDING OF GENDER EQUALITY - Yustinus Tarigan; Vinda Afnita (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Achieving the learning objectives of physical education itself leads to one very important aspect, namely the affective aspect, which emphasizes broadly to include social and emotional development and the formation of values and attitudes. Gender equality is one of the values and attitudes that physical education learning instills, this is important to build an understanding that the relationship between men and women at various levels of society, both formal institutions and informal institutions including family institutions have a gender responsive attitude so that gender equality is realized.